The synthesis of ethical decision making for business professionals in small and medium sized enterprises (SMEs) / Khalizani Khalid - Khalid, Khalizani (Institute of Graduate Studies, UiTM, 2014)
The new approach to the field of ethical decision research deals with integrating moral philosophy theories into moral development theory, theory of reasoned action, stakeholder theory, and ethical leadership theory to study ethical decision making among business professionals in Malaysian. This study aims to examine the factors influencing ethical decision making in SMEs that has received almost no attention and failed to be addressed in previous studies. To ensure the compatibility and relevancy of the survey items, cognitive interviews with SMEs business professionals and focus groups discussions with relevant stakeholders were employed to determine significant design problems, to reduce inherent problems, and to reduce social-desirability bias before the survey is finalized. 340 responses from SMEs business professionals were tested using structural equation modelling to determine the best fit model.